Examining Dyadic Developmental Psychotherapy as a Treatment for Adopted and Foster Children: A Review of Research and Theory. (November 2014) - Mercer, Jean
Dyadic developmental psychotherapy (DDP) is a mental health intervention intended primarily for children with problematic attachment histories. It has received increased attention in the United Kingdom and the United States in the last few years. DDP has been publicized as a research-supported treatment, but a review of research shows that it does not meet ordinary standards for this category. In addition, DDP appears to be based on a number of questionable metaphors that have been used in attempted explanations of personality development and mental illness. Some unanswered questions about the background assumptions of DDP are presented. Caution about this method of therapy is recommended.